2022
DOI: 10.1038/s43247-022-00413-w
|View full text |Cite
|
Sign up to set email alerts
|

Whole-system analysis reveals high greenhouse-gas emissions from citywide sanitation in Kampala, Uganda

Abstract: Global estimates of emissions of greenhouse gasses do not take into account the complex service chain in rapidly growing cities in low- and middle-income countries. This paper presents an end-to-end analysis to estimate emissions from all stages of the sanitation-service chain, using Kampala in Uganda as an example. We show that emissions associated with long periods of storage of faecal waste in sealed anaerobic tanks (49%), discharge from tanks and pits direct to open drains (4%), illegal dumping of faecal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The natural contribution of tropical riverine CO 2 fluxes to the global C budget is comparatively minimal (<600 Tg C yr −1 ). However, our findings are consistent with recent research showing that water quality degradation through increasing lentic/stagnant waters from river channelization, sewage treatment infrastructure, and pollution load in densely populated cities, could significantly strengthen the potential for river CO 2 outgassing [11][12][13]51]. Annual pCO 2 in the Day River was 1.8-fold higher than in the Red River and up to two-fold greater during the dry season than the median of pCO 2 in >20 sub/tropical rivers.…”
Section: Implications and Conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…The natural contribution of tropical riverine CO 2 fluxes to the global C budget is comparatively minimal (<600 Tg C yr −1 ). However, our findings are consistent with recent research showing that water quality degradation through increasing lentic/stagnant waters from river channelization, sewage treatment infrastructure, and pollution load in densely populated cities, could significantly strengthen the potential for river CO 2 outgassing [11][12][13]51]. Annual pCO 2 in the Day River was 1.8-fold higher than in the Red River and up to two-fold greater during the dry season than the median of pCO 2 in >20 sub/tropical rivers.…”
Section: Implications and Conclusionsupporting
confidence: 92%
“…To help mitigate these harmful effects introduced by urban development, we suggest carrying out responsive water course management actions to increase river flows in problem areas during the dry season [22,40], along with the implementation of green infrastructure that prioritize the natural hydrological functions of the river [54]. Improving sanitation infrastructure and management in urban centers [51] and strengthening the engagement with local government to exchange research findings and support policy making on water management, including sustainable agricultural development (e.g. use of fertilizers) [42], could further help reducing nutrient load and greenhouse gasses.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…We describe that long storage or retention times are necessary for disinfection; however, greenhouse gas emissions from fecal sludge can increase significantly with increased storage time. 141,142 Reid et al demonstrated that replacement to a low-CH 4 emission technologies (e.g., composting toilet) yields co-benefits for both greenhouse gas mitigation and water and sanitation development. 141 Second, some novel thermal treatment systems are not included that have gained traction in recent years, e.g., Omni Processors.…”
Section: The Limitations Of This Reviewmentioning
confidence: 99%
“…Transforming the river basin and hydrological characteristics may lead to eutrophication, hypoxia, HABs, and excess partial pressure of aquatic CO 2 (Wang et al 2017; Zhang et al 2021). Projected urban development in the Magdalena River basin will thus likely increase water demand intensifying stagnant waters, oxygen drawdown, and potentially associated HABs among urban tributaries, especially during dry periods (Johnson et al 2022).…”
Section: Water Pollution and Urbanizationmentioning
confidence: 99%